Strategies For Vocabulary Enrichment Employed By The Teacher At The Fifth Year Of SD N I Jatirejo, Girimarto, Wonogiri - Kurniawati, Witri (2012)
The subject of this research is the fifth year of SD N I Jatirejo in 2011/2012 academic year. The objectives of this research are: (1) to describe the strategies for vocabulary enrichment employed by the teacher at fifth year of SD N I Jatirejo, (2) to describe the problems faced by the fifth year of SD N I Jatirejo in vocabulary enrichment at applying the strategies, (3) to describe the problem solving which is used by the teacher of the fifth year of SD N I Jatirejo. The writer uses descriptive research. The writer gets the data of this research from event, informant, and documents. The events of this research are all of the activities in the classroom which is used in the strategies for vocabulary enrichment. Informants in this research are the English teacher and the students of the fifth year of SD N I Jatirejo. Documents in this research are all of the written information related to the strategies for vocabulary enrichment employed by the teacher at the fifth year of SD N I Jatirejo. The method of collecting data is observation, document and interview. After analyzing the data, the writer finds that (1) the teacher of the fifth year of SD N I Jatirejo uses definition, self-defining context, realia, reading the words, writing the words and games as the strategies for vocabulary enrichment, (2) the students of the fifth year of SD N I Jatirejo have some difficulties in vocabulary enrichment at applying the strategies, that are pronunciation and spelling, (3) the problem solving used by the teacher to solve the students' problems are by repeating to pronounce the words and also writing down the words on the blackboard in order the students can copy it.